2011
DOI: 10.1097/mot.0b013e3283467115
|View full text |Cite
|
Sign up to set email alerts
|

Hot topics in postsmall bowel transplantation: noninvasive graft monitoring including stool calprotectin and plasma citrulline

Abstract: These approaches and others are reviewed in an outline of the current progress towards developing a clinically useful noninvasive tool for graft monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Our previous works (6,7) were successfully validated by the data presented herein that were collected in a series of greater than 100 pediatric patients with close to 200 episodes of ACR, observed over an extensive period of time (up to 16 years). One of the limitations of our preliminary results was that we were not able to evaluate the timeliness of citrulline data as a forewarning of rejection due to lack of sufficient number of rejection episodes with paired citrulline samples drawn just before the biopsy (7,16). To circumvent this problem and assess the feasibility of citrulline to accurately 'predict' rejection in clinical practice, we carefully matched the date of citrulline measurement to the date of intestinal biopsy so that the corresponding histopathologic diagnoses followed citrulline values in a chronological order.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous works (6,7) were successfully validated by the data presented herein that were collected in a series of greater than 100 pediatric patients with close to 200 episodes of ACR, observed over an extensive period of time (up to 16 years). One of the limitations of our preliminary results was that we were not able to evaluate the timeliness of citrulline data as a forewarning of rejection due to lack of sufficient number of rejection episodes with paired citrulline samples drawn just before the biopsy (7,16). To circumvent this problem and assess the feasibility of citrulline to accurately 'predict' rejection in clinical practice, we carefully matched the date of citrulline measurement to the date of intestinal biopsy so that the corresponding histopathologic diagnoses followed citrulline values in a chronological order.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that citrulline is a useful marker for detecting moderate or severe ACR in a study including 37 pediatric and 20 adult intestinal recipients (7). However, the sensitivity and predictive value for detecting mild ACR were limited and insufficient citrulline data obtained immediately prior to biopsy with relatively small number of rejection episodes precluded the assessment of citrulline as a forewarning (7,16). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore while it is important to look for and document capillaritis and/or other vascular endothelial injury, their absence does not in any way exclude the diagnosis of severe ACR, a requirement in almost all other solid organ allografts. Lastly although this continues to generate potential candidates, 21 there are still no widely accepted clinically useful serum markers of ACR for small intestine. The only clinical context therefore available to the pathologist relates to the patient's symptoms, age of graft, and changes in immunosuppression, endoscopic findings, as well as viral (e.g.…”
Section: Small Intestinementioning
confidence: 98%
“…It is recommended to perform systemic biomarker evaluation concomitant with histopathological examination. Among auxiliary assays, increase in use of measurements of citrulline level in the blood, cytofluorographic analysis of peripheral immune cell population, cytokine profiles, and the quantitation of distinct gene set changes have been observed (33)(34)(35). Developments in the understanding of genes promise to provide; limited gene sets taken from blood or from intestinal biopsies to enhance pathological diagnosis of rejection.…”
Section: Immune Monitoringmentioning
confidence: 99%
“…Citrulline is a protein released from enterocytes and levels of citrulline show negative correlation with the function of the small bowel graft (33). From its enterocyte-specific origin, it first gained interest in intestinal failure as a marker.…”
Section: Stool Testsmentioning
confidence: 99%